Galeus corriganae sp. nov., a new species of deepwater catshark (Carcharhiniformes: Pentanchidae) from Papua New Guinea - White, William T.; Mana, Ralph R.; Naylor, Gavin J.p. (Zootaxa, 2016)
A new species of catshark, provisionally placed in the genus Galeus, is described from Papua New Guinea based on 7 specimens collected during recent deepwater surveys of the region. The new species, Galeus corriganae, is closest to G. priapus from New Caledonia and G. gracilis from northwestern Australia but differs in several morphological characters. A reclassification of the catshark groups is required to revise the familial and generic arrangement of the group.